2012
DOI: 10.1186/1743-7075-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The chronic effects of fish oil with exercise on postprandial lipaemia and chylomicron homeostasis in insulin resistant viscerally obese men

Abstract: BackgroundVisceral obesity and insulin resistance are associated with a postprandial accumulation of atherogenic chylomicron remnants that is difficult to modulate with lipid-lowering therapies. Dietary fish oil and exercise are cardioprotective interventions that can significantly modify the metabolism of TAG-rich lipoproteins. In this study, we investigated whether chronic exercise and fish oil act in combination to affect chylomicron metabolism in obese men with moderate insulin resistance.MethodsThe single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…It has been well established that the consumption of n ‐3 PUFA (Slivkoff‐Clark et al . ; Anderson et al . ; Colussi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that the consumption of n ‐3 PUFA (Slivkoff‐Clark et al . ; Anderson et al . ; Colussi et al .…”
Section: Discussionmentioning
confidence: 99%
“…) and the concentration of pro‐atherogenic chylomicron remnants (Slivkoff‐Clark et al . ), occur following a combined n ‐3 PUFA and exercise intervention. In addition, the consumption of flaxseed, which is high in ALA, in combination with exercise training, has been shown to improve plasma lipoprotein levels, oxidative stress and inflammation in a model of myocardial ischaemia (Naounou et al .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, while Tinker et al 133 showed that postprandial TRL apoB reduction is likely caused by omega-3 fatty acid mediated suppression of both hepatic and intestinal apoB secretion/synthesis, Slivkoff-Clark et al 134 showed that fish oil independently improved plasma TG homeostasis but did not resolve hyper-chylomicronemia. Instead, combining fish oil with chronic exercise reduced the plasma concentration of pro-atherogenic CM remnants 134 ; in addition it reduced the fasting and postprandial TG response in viscerally obese insulin resistant subjects 134 . In nonobese subjects a high-fish diet decreased TRL apoB48 concentration by reducing the secretion rate and the fractional catabolic rate of apoB48 135 .…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 98%
“…The mechanism of exercise-induced LPL activity remains unclear, but it was hypothesized that exercise stimulates especially muscular LPL activity, although this could not be confirmed in a recent study [125]. A 12-week walking program supplemented with fish oil (1000 mg eicosepantenoic acid and 700 mg docosahexaenoic acid daily) in subjects with the MetS resulted in lower fasting TG and decreased the postprandial response of TG and apoB48 [126]. Exercise training for 16 weeks in obese subjects with NAFLD resulted in a small reduction in intra-hepatic TG content, although no changes in VLDL-TG or apoB100 secretion were observed [127].…”
Section: Lifestyle Interventions For Dyslipidemia In Obesitymentioning
confidence: 99%